The relationship between work-family interface and turnover intention: a study in a sample of Italian nurses - Ghislieri, Chiara; Molino, Monica; Gatti, Paola (La Medicina del Lavoro, 2015)
Background: Work-family interface is an increasingly central research topic in organizational studies, and it is considered particularly relevant in healthcare contexts. Several studies on nursing staff showed the role of work-family conflict (WFC) and enrichment (WFE) in influencing work dynamics. Objectives: The present study aims at examining the relationship between work-family interface (in terms of conflict and enrichment) and turnover intentions (TI), in a sample of Italian nurses. Methods: A sample of 478 nurses filled in a self-report questionnaire, consisting of different scales based on the international literature. Results: Regression analysis, with TI as dependent variable, showed a positive relationship with WFC and a negative relationship with WFE. Conclusions: The results of the study confirmed that WFC was a potential predictor of TI, able to influence the tendency to desire a new job and look for a new occupation. WFE also had a role in influencing this outcome: perceptions of enrichment from work to family can contribute to reducing TI. The results of the present study indicate the importance of developing working contexts that will foster work-family conciliation, through policies and practices able to reduce the negative interference from work to family, and to increase opportunities to improve and develop new skills that can be used also in other contexts.